Assets Debt and the Drawdown of Housing Equity by an Ageing Population - Ong, Rachel; Haffner, M.; Wood, G.; Jefferson, Therese; Austen, Siobhan (Australian Housing and Urban Research Institute (AHURI), 2013)
This Positioning Paper is the first output of a project that aims to uncover the uses, financial costs and risks of housing equity withdrawal (HEW) via alternative mechanisms by older Australians.